Orientation towards the Future among Middle School Students - Mohsen Al-Zarkoshi, Samir Idan; Aziz Al-Khashmani, Awan Kazem (Journal of Tikrit University for Humanities, 2023)
This study answers the following questions to determine middle school pupils’ future orientation: 1-To assess middle schoolers’ future orientation. 2- Assessing middle school students future orientation by gender. 3- Assessing middle school students. future direction by specialism (literary, scientific). The present study is confined to students of the fifth preparatory schools linked to the Directorate of Education of Jalawla in Diyala Governorate, of both sexes (males-females) and specialties (scientific-literary) for the 2022-2023 academic The study sample includes 400 male and female students from 11 schools: 5 girls, 4 boys, and 2 mixed. The researcher created the future orientation measure to meet study goals. Content validity, apparent validity, and logical validity were used to verify the scale’s validity and determine its items’ discriminating power. The re-test and Cronbach’s alpha methods were used to determine stability for both scales, and the data were statistically processed using SPSS. Research findings: The present research’s findings agreed and varied from other prior studies owing to the sample’s situations and experiences. In middle school, pupils are focused on the future. 2- Statistically significant variations in future orientation exist between sexes, favoring men. 3- There are no substantial variations in future direction based on specialty (scientific-literary).